Moderate Drought Stress Affected Root Growth and Grain Yield in Old, Modern and Newly Released Cultivars of Winter Wheat - Fang, Yan; Du, Yanlei; Wang, Jun; Wu, Aijiao; Qiao, Sheng; Xu, Bingcheng; Zhang, Suiqi; Siddique, Kadambot H. M.; Chen, Yinglong (Frontiers in Plant Science, 2017)
To determine root growth and grain yield of winter wheat (Triticum aestivum L) under moderate drought stress, a nursery experiment and a field trial were conducted with or without water stress using three representative cultivars released in different years: CW134 (old landrace), CH58 (modern cultivar) and CH1 (new release). In the nursery experiment, plants were grown in soil-filled rhizoboxes under moderate drought (MD, 55% of field capacity) or well-watered (WW, 85% of field capacity) conditions. In the field trial, plots were either rainfed (moderate drought stress) or irrigated with 30 mm of water at each of stem elongation, booting and anthesis stages (irrigated). Compared to drought stress, grain yields increased under sufficient water supply in all cultivars, particular the newly released cultivar CH1 with 70% increase in the nursery and 23% in the field. When well-watered (nursery) or irrigated (field), CH1 had the highest grain yields compared to the other two cultivars, but produced similar yield to the modern cultivar (CH58) under water-stressed (nursery) or rainfed (field) conditions. When exposed to drought stress, CW134 had the highest topsoil root dry mass in topsoil but lowest in subsoil among the cultivars at stem elongation, anthesis, and maturity, respectively; while CH1 had the lowest topsoil and highest subsoil root dry mass at respective sampling times. Topsoil root mass and root length density were negatively correlated with grain yield for the two water treatments in nursery experiment. When water was limited, subsoil root mass was positively correlated with thousand kernel weight (TKW). In the field trial, CH1 and CH58 used less water during vegetative growth than CW134, but after anthesis stage, CH1 used more water than the other two cultivars, especially in the soil profile below 100 cm, which was associated with the increased TKW. This study demonstrated that greater root mass and root length density in subsoil layers, with enhanced access to subsoil water after anthesis, contribute to high grain yield when soil water is scarce.